2005
DOI: 10.1007/s00299-005-0965-5
|View full text |Cite
|
Sign up to set email alerts
|

In vitro somatic embryogenesis from cell suspension cultures of cowpea [Vigna unguiculata (L.) Walp]

Abstract: We report, an efficient protocol for plantlet regeneration from the cell suspension cultures of cowpea through somatic embryogenesis. Primary leaf-derived, embryogenic calli initiated in MMS [MS salts (Murashige and Skoog 1962) with B5 (Gamborg et al. 1968) vitamins] medium containing 2,4-Dichlorophenoxyacetic acid (2,4-D), casein hydrolysate (CH), and L: -Glutamic acid-5-amide (Gln). Fast-growing embryogenic cell suspensions were established in 0.5 mg l(-1) 2,4-D, which resulted in the highest recovery of ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 48 publications
3
28
1
1
Order By: Relevance
“…To improve embryogenesis in eucalyptus, glutamine and casein have been employed (Pinto et al, 2002), while in Miscanthus and Cherries cultures, 1-proline is studied to boost up early stages of somatic embryogenesis (Holme et al, 1997;Cheong and Pooler, 2004). The accumulation of amino acids during somatic embryogenesis was also reported for alfalfa, Anise (Andarwulan and Shetty, 1999), cowpea (Ramakrishnan et al, 2005) and for the shoot regeneration of strawberry (Qin et al, 2005). Moreover, Zhang et al (2006) reported that the transcription levels persuaded by TDZ were observed to vary all over TDZ treatment.…”
Section: Amino Acidsmentioning
confidence: 99%
“…To improve embryogenesis in eucalyptus, glutamine and casein have been employed (Pinto et al, 2002), while in Miscanthus and Cherries cultures, 1-proline is studied to boost up early stages of somatic embryogenesis (Holme et al, 1997;Cheong and Pooler, 2004). The accumulation of amino acids during somatic embryogenesis was also reported for alfalfa, Anise (Andarwulan and Shetty, 1999), cowpea (Ramakrishnan et al, 2005) and for the shoot regeneration of strawberry (Qin et al, 2005). Moreover, Zhang et al (2006) reported that the transcription levels persuaded by TDZ were observed to vary all over TDZ treatment.…”
Section: Amino Acidsmentioning
confidence: 99%
“…Previous studies suggest use of auxins at initial stage like 2,4,5-trichlorophenoxyacetic acid, (Muthukumar et al, 1995); 2,4-D (Ganapathi and Anand, 1998;Prem Anand et al, 2000 andRamakrishnan et al, 2005) followed by culturing on cytokinin-auxin combinations for induction of callus and somatic embryogenesis in cowpea. Pulse treatment with cytokinins for shoot induction in cowpea using BAP at higher dose has also been reported by Brar et al (1999) and Aasim et al (2009a).…”
Section: Introductionmentioning
confidence: 99%
“…Cowpea, like most legumes, is recalcitrant to in vitro regeneration, which limits its potential for improvement through genetic manipulations (Ramakrishnan et al, 2005). Furthermore, variability is involved in almost every aspect of the regeneration systems explored, such as optimal explant tissues, basal salt compositions, plant growth regulators, sucrose levels, and variation in composition of gelling agents (agar or Gelrite) (Pellegrineschi, 1997;Popelka et al, 2006;Aasim et al, 2009a).…”
Section: Introductionmentioning
confidence: 99%